Comparison of Clinical Outcome following Cartilage Repair for Patients with Underlying Varus Deformity with or without Additional High Tibial Osteotomy: A Propensity Score–Matched Study Based on the German Cartilage Registry (KnorpelRegister DGOU). (December 2021) - Faber, Svea; Angele, Peter; Zellner, Johannes; Bode, Gerrit; Hochrein, Alfred; Niemeyer, Philipp
Background: Even though realignment procedures have gained popularity as concomitant techniques in cartilage repair approaches with underlying malalignment, the clinical efficacy has not been proven to full extent. Methods: Out of 5474 patients from the German Cartilage Registry, 788 patients with focal cartilage defects on the medial femoral condyle having received either no accompanying surgery or high tibial osteotomy (HTO) were identified. After a 1:1 propensity score matching, outcome of 440 patients was evaluated using KOOS (Knee Injury and Osteoarthritis Outcome Score), VAS (visual analogue scale), and satisfaction during the 3-year follow-up. Results: Patients having received a concomitant HTO had significantly higher postoperative KOOS values (12 months: 67.26 ± 15.69 vs.75.10 ± 16.12, P = 0.001; 24 months: 67.14 ± 23.85 vs. 77.11 ± 16.50, P = 0.010; 36 months: 74.40 ± 16.57 vs. 81.75 ± 14.22, P = 0.023) and lower pain levels (6 months: 3.43 ± 2.18 vs. 2.89 ± 2.15, P = 0.009; 12 months: 3.64 ± 2.20 vs. 2.17 ± 1.96, P < 0.001; 24 months: 4.20 ± 3.12 vs. 2.94 ± 2.45, P = 0.005; 36 months: 3.20 ± 2.18 vs. 2.02 ± 1.98, P = 0.003). One and 3 years postoperatively, concomitant HTO led to significantly higher satisfaction in patients. These advantages of accompanying HTO were also seen in the group of patients with a varus deformity of 5° or more, in which pain levels without concomitant HTO even increased during the 3-year follow-up. Conclusion: The results of the present study underline the importance and safety of concomitant HTO in patients with cartilage defects and varus deformity. HTO should therefore be considered and recommended generously in patients with focal cartilage defects of the medial femoral condyle and varus deformity.